Using Humorous Communication in Learning English As the Second Language - Wahyuni Wahyuni (EDUVELOP, 2017)
Language teachers are often encouraged to use humor in the classroom. Humor is presented as socially and psychologically beneficial to learners, helping to relax them, to create a comfortable classroom atmospher, to create bonds classmates, to raise student interest, and simply to make learning more enjoyable. Using humorous communication in learning English as the second language is effective way to improve the students’ interest and ability because humor is able to craete the learning becomes more varied and more vivid, feels the strain when learning can be reduced, creating communication that familiar, strech the nervous strained into rilex, and creating the attractiveness of learning. The purpose of the study is to find out the students’ interest and ability in English. The method used in this research was quasi-experimental design, it is assigned two groups namely experimental and control group. To collect the data, the researcher used three instruments, they are interview, participant observasition, and discourse analysis of the audiotaped and videotaped interaction. The result show that there is differences interest and ability before and after leaning English though humour. Thus, it is recomended for all English teachers to improve students’ interesrest and English ability as the second language.